The Impact of Government Debt Issuance on Short-Term interest rates in Indonesia - Sri Adiningsih (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
This paper analyzes whether the expansionary fiscal policy funded by issuing debt instruments in financial markets will increase short-term interest rates. If the expansionary fiscal policy increases interest rates, which decrease private spending especially investment, crowding out occurs. This is interesting because global economic crisis has encouraged many countries to run large budget deficits to stimulate the economy. Indonesia has also run budget deficit during this crisis and even in years before. The impact of such a policy can be significant because Indonesia’s debt market is still narrow and shallow. Therefore, its capability of absorbing the government debt instruments without influencing the private sector funding is limited. This study tests whether the crowding out occurs in Indonesia using a time series econometric model inspired by Cebula and Cuellar’s model. The Cointegration Regression and Error Correction Model (ECM) are used in this study. Monthly data from April 2000 to December 2008 are used for overnight real interbank call money interest rates, real net government bond issues in trading, real narrow money supply, real rate of one-month Certificate of Bank Indonesia, growth of Gross Domestic Product, and real net international capital flows. This empirical study shows that the crowding out problem occurred in Indonesia during the period. This indicates that financing budget deficit in Indonesia by issuing debt instruments in the financial markets has a negative impact on the private sector.